Theology and Sports: Sport in the Educational System of Saint John Bosco - Zbigniew Dziubiński (Seminare)
The aim of the article is to show the synergy between theology and sport on the example of the educational system of Saint John Bosco created by him during his formation and pedagogical practice aimed at young people, especially the poor and neglected in intellectual, social, cultural and religious terms. The article presents the role and importance of sport in the educational system of the teacher from Turin, along with its enormous fitness and health, socio-cultural, psychological-interactional and ethical-religious potential. The analysis of the collected material shows that sports activity in the preventive system is not an addition or an insignificant decoration that can make the system image more attractive, but the foundation on which subsequent layers of the pedagogical system are built. Therefore, it may be concluded that sports activity was not included on the basis of generous voluntary action, but as an integral and complementary, necessary and inalienable element, serving the comprehensive, harmonious and holistic development of children and youth.